As revoltas e seu impacto sobre a comunicação pública: o potencial do Observatório Participativo da Juventude - Rothberg, Danilo [UNESP]; Luvizotto, Caroline Kraus [UNESP]; Vanzini, Kátia Viviane da Silva [UNESP] (Liinc em Revista, 2014)
The Participatório: Observatório Participativo da Juventude (Participatory: Observatory on the Youth Participation) is an online platform created in August 2013 as part of the response of the General Secretariat of the Presidency of the Republic of Brazil to the protests which took Brazilian streets in the middle of that year. This paper analyses the Participatório against the theoretical context brought by studies of digital activism and social movements. We revise relevant theories and present results of an empirical study indicating parameters to assess whether the apparent goals of the platform would have been reached. The data suggest that the initiative could achieve its purposes as long as it secures the efficacy of future improvements.

O Participatório: Observatório Participativo da Juventude é uma plataforma online lançada em agosto de 2013 como parte da resposta da Secretaria Geral da Presidência da República aos protestos que tomaram as ruas brasileiras em meados daquele ano. Com o objetivo de situar a proposta do Participatório diante do contexto teórico trazido pelos estudos de movimentos sociais e ativismo digital, este artigo reúne teorizações pertinentes e apresenta resultados de estudo empírico que indica balizas para avaliar se as metas aparentes da plataforma teriam sido atingidas. Os dados sugerem que a consecução dos objetivos da iniciativa dependerá da eficácia de aperfeiçoamentos futuros.
The June protests and their impact on public communications: the potential of the Observatory on Youth Participation
Keywords: Social Movements; Social Networks; Digital Activism; Political; Movimentos sociais; Redes Sociais; Ativismo digital